2020
DOI: 10.3390/robotics10010006
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of a Robotic Approach for the Gluing Process in the Footwear Industry

Abstract: Manufacturing processes in the shoe industry are still characterized to a large extent by human labour, especially in small and medium craft enterprises. Even when machinery is adopted to support manufacturing operations, in most cases an operator has to supervise or carry out the task. On the other hand, craft footwear industries are called to respond to continuous challenges to face the globalization effects, so that a rapid adaptability to customer needs is required. The industry 4.0 paradigms, which are ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In response to the above problems, this study considers the problem of task scheduling in robotized adhesive dispensing. It is worth mentioning that problems of this type have been quite seldom investigated in previous studies [30,31,32] and that the approach employed in this work is an alternative to the methods reported in the literature.…”
Section: Robotic Task Schedulingmentioning
confidence: 99%
“…In response to the above problems, this study considers the problem of task scheduling in robotized adhesive dispensing. It is worth mentioning that problems of this type have been quite seldom investigated in previous studies [30,31,32] and that the approach employed in this work is an alternative to the methods reported in the literature.…”
Section: Robotic Task Schedulingmentioning
confidence: 99%
“…Recently, automated gluing applications have become very popular with the development of new industrial machines and tools, which can be efficiently utilized by collaborative robots. The majority of the work focuses on defining the robot trajectories based on the CAD description of the industrial object (Castelli et al, 2021). Other approaches, utilize simple Cartesian space industrial manipulators coupled with computer vision (Pagano et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Analyzing the state of the art about the automation of the bonding process in the footwear industry, different research works related to the operation can be found, mainly for gluing application systems, using cartesian robots and a vision system [5], [6], or anthropomorphic robotic arms to spray the outsole [7]. References can also be found about systems for applying adhesive to the shoe upper using adhesive extrusion systems [8], as well as about other systems to deposit glue so as to wet the shoe upper controlling the force between the glue extruder and the surface of the shoe upper during the application [9]. Different approaches can also be identified to automate footwear manufacturing plants from the 3D CAD information of the footwear model [10], but results are not particularly satisfactory or limited to the large-scale manufacturing; however, given the specific characteristics of this sector, where short series of shoe models are usually manufactured and different sizes and feet (right and left) must be considered, fully automating a plant is particularly challenging.…”
Section: Introductionmentioning
confidence: 99%